BASIC LIFE SUPPORT TRAINING TO IMPROVE COMPETENCY FOR NURSING STUDENTS IN HANDLING CARDIAC ARREST PATIENTS: A SYSTEMATIC LITERATURE REVIEW - Fariz Jauhar Muslim (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Introduction:Cardiovascular diseases are the leading cause of death globally, with sudden cardiac arrest requiring immediate action during the critical period to prevent irreversible damage. Nursing students must be highly trained in Basic Life Support (BLS), particularly in cardiopulmonary resuscitation (CPR), to effectively manage emergency situations. Method: This study employed a systematic literature review using the PICOT framework to analyze five peer-reviewed articles published between 2021 and 2025. The articles, sourced from Google Scholar and PubMed, examined the impact of BLS training on nursing students through quasi-experimental pre–posttest designs. Result:The results consistently showed significant improvements in students' knowledge, technical skills, and readiness following BLS training. Simulation-based teaching, led by certified instructors, effectively enhances both cognitive and psychomotor skills. Discussion: The observed low baseline competency prior to training underscores the necessity of integrating BLS into nursing curriculum. Ongoing simulation-based instruction is crucial for promoting clinical preparedness and building confidence among nursing students. Conclusion: BLS training substantially improves nursing students' ability to perform CPR. It is strongly recommended that nursing education institutions adopt regular and structured BLS training programs to ensure the preparedness of future healthcare professionals.